Sustaining traditional food: consumers' perceptions on physical characteristics of keropok lekor or fish snack - Omar, M.; Mohd Adzahan, Noranizan; Mohd Ghazali, Hasanah; Karim, Roselina; Abdul Halim, N. M.; Abdul Karim, Muhammad Shahrim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Keropok Lekor or frankfurter-like snack has long existed in Malaysia and has been sold in commercial retail shops as well as on the streets. The aims of this study were to analyze consumer's perception and attitude towards keropok lekor and to determine consumer's behavior on the product. Survey questionnaire was employed as a data collection tool. A total of 212 respondents from a university participated in this study. Results showed that more than 70% of the respondents chose to eat keropok lekor because of the taste. Half of the respondents chose black pepper as an innovative supplementary flavor of keropok lekor. This study also explores and analyses preliminary consumer behavior about keropok lekor such as satisfaction level, factors that drive consumption, product's image from consumer perspectives and etc.